AI-Driven Adaptive Learning to Enhance Digital Literacy Integrated with Mental Health Support of Teen Learners - Nurul Kholisatul (Jurnal Nasional Pendidikan Teknik Informatika: JANAPATI, 2026)
The rapid advancement of digital technology has significantly transformed education worldwide, including in Indonesia. Artificial intelligence (AI) is increasingly used to create personalized, adaptive, and interactive learning experiences. Despite high exposure to technology, many high school and vocational students still struggle with digital literacy and mental well-being. This study proposes DigiMind, an AI-driven adaptive learning system that integrates digital literacy with mental health support to promote balanced and inclusive learning. Using a mixed-method approach, the study involved 146 students and 10 teachers from two partner schools in Surakarta. Quantitative data were collected through surveys based on the UNESCO Digital Literacy Framework and ICT Watch Indonesia, while qualitative data were obtained from focus group discussions (FGD) with teachers and students. The findings indicate that although 98.6% of students have used AI-based learning tools, many lack awareness of data privacy, digital ethics, and focus management. About half experienced digital fatigue, while most emphasized the need for well-being features such as break reminders, relaxation content, and adaptive materials. Teachers, in contrast, prioritized monitoring, analytics, and early stress detection—revealing a dual orientation between student engagement and teacher support.The resulting DigiMind blueprint combines adaptive learning modules, AI-based mental health analytics, and dual dashboards for students and teachers. Expert validation confirmed its pedagogical, technical, and psychological feasibility. Overall, integrating digital literacy and digital well-being within AI-driven adaptive learning enhances both cognitive performance and emotional resilience, offering a holistic model for sustainable digital education in Indonesia